pH Evaluation of some Skin Cleansers in Sabratha, Libya - Tariq M. Hassan; Rouida M. Hassan; Wafa A. Aldeeb (African Journal of Advanced Pure and Applied Sciences, 2022)
The present investigation was carried out to determine the pH values of some Skin Cleansers in Sabratha, Libya. Twenty-four different Samples of branded shower gel, liquid soap and shampoos, were random collected. According to the standard method ASTM D1172, pH values were measured using WTW-Multiline P4 pH meter. The experimental obtained results were analyzed and presented graphically. The majority pH values of shampoo were acid balanced and the rest of shampoo samples tend to be neutral. 50% of the pH values of Shower gel and liquid soap were acidic and the other 50% of the pH values tend to be neutral. The majority pH values of shampoo were acid balanced and the rest of shampoo samples tend to be neutral. 50% of the pH values of Shower gel and liquid soap were acidic and the other 50% of the pH values tend to be neutral.